Nieczytelność oświadczenia o stanie majątkowym jako przesłanka do stwierdzenia jego bezskutecznego złożenia - Jaworski, Arkadiusz (Studia Prawa Publicznego, 2024)
Declarations of ﬁnancial interests are considered one of the key elements of the Polish anti-corruption system. Unfortunately, due to the negligence of the legislator, there are often numerous practical problems that control authorities have to deal with. One of them is the illegibility of the submitted declarations, which makes it impossible to verify their content. This is a serious shortcoming that makes it difficult to control persons holding public functions and can be used to circumvent the imposed obligations. This text considers whether, despite the lack of detailed regulations regarding the “style” of completing the declaration of interests, control authorities are forced to accept documents that cannot be veriﬁed. In the author’s opinion, the directive of a rational legislator requires just the opposite, in order to ensure the effectiveness of such key provisions from the point of view of democracy as anti-corruption provisions. Refusal to accept the declaration should be made by applying, by analogia legis, the provisions of art. 64. § 2 of the Code of Adminisrative Procedure – by ﬁnding a formal deﬁciency and requesting its correction. The criterion of readability itself should be based on the pattern of the average recipient, developed on the basis of the principles of knowledge, life experience and logical reasoning. This position, supported by case law and general principles of administrative proceedings, allows for the proper functioning of this element of the anti-corruption system, while protecting the rights of the obliged person.